Tren Computational Thinking in Mathematics Education: A Global Bibliometric Analysis 2016-2025 - Majid, Majid (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to identify the trends of annual publications, the linkages of keywords and thematic clusters, the patterns of collaboration between authors and institutions, as well as the most prolific and influential authors in the study of Computational Thinking (CT) in the field of mathematics education over the past decade. Data is collected from the Scopus database using relevant keywords, then analyzed through the VOSviewer software to map the relationships between keywords, authors and documents. The results of the analysis showed a significant increase in the number of publications from year to year, with the five most prolific authors being Ng, Oi-Lam; Barendsen, Erik; Drijvers, Paul; Gadanidis, George; and Maharani, Swasti. The focus of the research is divided into five main thematic clusters, namely the perspective of students and teachers on CT, the development of CT assessment instruments, the integration of CT in mathematics learning, systematic studies related to CT-based learning models, as well as publication trends and bibliometric studies. These findings confirm the important role of CT in improving the quality of 21st century mathematics learning. Recommendations for further research include the development of CT-based pedagogical models for different levels of mathematics education, the exploration of students' affective and metacognitive aspects in CT learning, as well as the development of more specific and contextual CT assessment instruments for mathematics learning.